Egy elmulasztott történelmi lehetőség az osztrák-magyar gyarmatosítás - Nagy Miklós Mihály (2010)
The newly founded Austro-Hungarian Monarchy was trying to step up as a great power at the political arena of the World and of Europe. As far as diplomatic relations were concerned, it followed the model of the great powers of that time and simultaneously created such armed forces that allowed this aim to became a reality. However the means and the objectives got into conflict because despite the Monarchy had the means to acquire colonies it did not build a colonial empire like other great powers did. This contradiction was even increased as the Habsburg Empire had sporadic colonies, also had colonizer dependents and the issue of colonialism rose in Hungary after 1867. We know colonizer soldiers from Hungarian military history although the Hungarian Kingdom had never have colonies. Missing colonization fundamentally determined the defeat of the Austro-Hungarian Monarchy in the First World War.